Revising: Sociologica as an International Journal for Sociological Debate - Elena Esposito; Flaminio Squazzoni; David Stark (Sociologica, 2022)
In this essay the editors-in-chief reflect on recent development of the journal and introduce the Symposium on Revising. We at Sociologica do not aim to be a major journal of sociology, but we do aspire to be a leading journal. Here we briefly gesture to four areas in which we aspire to leadership. These include: identifying vital topics for sociological debate; offering an alternative editorial model where the review process is not regarded as gate keeping; promoting greater diversity of formats for presenting sociological ideas beyond the one-size-fits-all model of Introduction – Theory – Data & Methods – Findings – Discussion – Conclusion; and presenting critical reflections on the practice of sociology.